Chinchero: ¿APP u obra pública? He ahí el dilema. Análisis crítico del régimen jurídico de las Asociaciones Público-Privadas y el de los contratos de obra pública a propósito del caso del Aeropuerto de Chinchero - Chinchay Yancunta, Camila (2017)
This article focuses on the concrete study of two forms of public infrastructure construction in our country: Public Private Partnerships and public works contracts, analyzing their characteristics, implications, differences and how they are regulated. Also, it realizes a critical analysis of the specific case of the contract of concession of the Chinchero’s airport and the signing of the respective addendum, concluding that the addendum meant the denaturing of the PPP and suggesting some proposals about this case.